EFEKTIVITAS METODE PEMBELAJARAN NUMBERE HEADS TOGETHER (NHT), TEAM ASSIST INDIVIDUALIZATION (TAI ) DAN CERAMAH TANYA JAWAB TERHADAP HASIL BELAJAR GEOGRAFI SISWA KELAS X SMA NEGERI 2 BOYOLALI TAHUN 2011/2012 - Nusantara, Mega (Pendidikan Geografi, 2013)
ABSTRAKThe aims of this research was to know: (1) The difference learning result between NHT method, TAI, with Lecture Question Answer (2) The difference learning result between NHT method with TAI (3) The difference learning result between NHT learning method with Lecture Question Answer (4) The difference learning result between TAI method with Lecture Question Answer. The result of this research : (1) There were difference the significant learning result between NHT method, TAI, with Lecture Question Answer. With Tcount > Ttable (17.941 > 3.088) (2) There were difference the significant learning result between NHT method with TAI. With Tcount > Ttable (3.978 > 3.82). (3) There were difference \ the significant learning result between NHT method with Lecture Question Answer learning. With Tcount > Ttable (8.466> 3.82) (4) There were difference the significant learning result between TAI method with Lecture Question Answer. With Tcount > Ttable (4.488 > 3.82).Kata Kunci: efektivitas, hasil belajar, metode kooperatif